Samīr Naqqāsh: Between the sacred and the demonic - Elimelekh, Geula (Studia Orientalia Electronica, 2015)
This paper describes some of the exilic literary issues that preoccupied the Jewish-Iraqi author Samīr Naqqāsh (1938–2004), who emigrated from Iraq to Israel at age thirteen, yet eschewed Hebrew and wrote only in Arabic. Though Naqqāsh’s characters were mainly Jewish, his stories project a natural universalism. A product of the twentieth-century world of upheavals and existentialism, he experienced the troubled existence of one severed from his roots and left without Providence, meaning or purpose. The present article argues that unifying theme that operated throughout his life and in all his fiction was that modern humanity has lost its way in a labyrinthine realm between the sacred and the demonic.